Profils des entreprises utilisatrices de voitures de société en Région de Bruxelles-Capitale - Thomas Ermans (Brussels Studies, 2017)
Based on the data from the company travel plans for BCR (2014), we have highlighted three profiles of companies which use company cars. They are defined as any company with at least 10 company cars for 100 workers – a threshold which excludes almost all public administrations as well as the health and education sectors. Beyond the elaboration of specific profiles, this factsheet highlights the correlation and association between the provision of company cars for workers and other characteristics. Specifically, along with the provision of parking spaces and poor accessibility by public transport, the provision of company cars contributes to creating mobility profiles at company level which are mainly focused on the use of cars for travel between home and work...